PENERAPAN MODEL PEMBELAJARAN GAME BASED LEARNING TERHADAP PENINGKATAN KEMAMPUAN BERHITUNG MATEMATIKA SISWA SEKOLAH DASAR - Astuti, Nadya; Widyatiningtyas, Reviandari; Rahman, Sidiq Aulia (Universitas Islam Nusantara, 2025)
This study aims to describe the application of the Game Based Learning model to improve the math counting skills of grade II students in elementary schools, especially in subtraction operations. The background of this research is the finding of problems in the field that the math arithmetic skills of grade II students are still relatively low, the problem is thought to be due to the lack of students' willingness to work on math problems. This study used a quasi-experimental method, with a research design of Nonequivalent Control Group Design, because the sampling used purposive sampling technique or sampling was not randomized. The research instruments used are observation and tests. The nature of the research used is quantitative, so data analysis is carried out using statistical tests with the help of IBM SPSS 22 software. The tests carried out are normality test, homogeneity test, t test, and N-Gain test. The results showed that there was an increase in the math counting ability of grade II students in elementary schools after the application of the Game Based Learning learning model. In addition, there is a significant difference in students' math counting skills between the experimental class using the Game Based Learning learning model and the control class using the conventional model. The application of Game Based Learning also shows the involvement and active participation of students.